Induction of Drosophila behavioral and molecular circadian rhythms by temperature steps in constant light. - Yoshii, T.; Fujii, K.; Tomioka, K. (Journal of Biological Rhythms, 2007)
In constant light, where Drosophila rhythms are normally disrupted, temperature cycles induce circadian rhythms at both the molecular and behavioral level. The authors investigated the process by which the thermoperiod induces the rhythms using temperature steps. A 10 degrees C temperature step-up induced a single locomotor activity peak ca 9 h after the temperature transition, whereas a 10 degrees C step-down induced a strong activity peak ca 24 h after the transition, and the peak recurred for several cycles, suggesting that the underlying clock is reset. Arrhythmic per(01) , tim( 01) , dClk(Jrk) , and cyc(01) mutant flies failed to show the rhythm after the step-down, suggesting that per, tim, dClk, and cyc are necessary for the step-down-induced rhythm. After the step-up, per(01) flies exhibited an activity peak similar to that of wild-type flies, suggesting that the peak can be induced by the step-up in absence of PER. mRNA levels of per, tim , dClk, vri, and Pdp1epsilon were changed in response to the temperature steps, but the changes differed depending on the direction of temperature steps, suggesting that steps-up and steps-down have different roles in the initiation of the oscillation. Probably, alternating 12-h temperature steps-up and steps-down will induce opposite changes in mRNA levels of clock genes, eventually producing stable molecular oscillations. Although TIM shows responses to temperature consistent with the changes of its mRNA, this is not the case for PER, consistent with posttranscriptional regulation. Changes of the mRNA levels were significantly altered but still observed in per( 01) flies but not observed in dClk(Jrk) flies, except for per mRNA. This suggests that dCLK is involved in the temperature-induced changes in the levels of most clock gene mRNA but that per is regulated via a different mechanism.